Students’ Perspective in the Use of TED Talks in Speaking Class - Citra Puteri Utami; Lia Noviana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Speaking skill is a person's skill to express an idea or ideas in front of many people verbally. Speaking skills also include vocabulary, grammar, and pronunciation to communicate. The ability to speak is important to have when it can build our confidence in communicating with others. In addition, when we become a teacher, we must pay attention to our speaking skills toward them, so that they will understand what we are saying. In online learning during the pandemic situation, lecturer can use a digital tool for teaching speaking. It is TED Talks. TED Talks are videos that present a great idea in 18 minutes or less. The purpose of this study is to know students' perceptions or opinions about the use of TED Talks in speaking class. The participant in this study is fifth semester students. The data will be gathered from questionnaire. This study uses a survey method. The result of this study will show whether the students like or dislike in using TED Talks in speaking class.